A Muslim voice in Victorian Britain: conversion and strategies of encounter in W.H. Abdullah Quilliam's poetry. (2nd January 2019) - Kindermann, Martin
ABSTRACT: The article examines poetic representations of the conversion experience by W.H. Abdullah Quilliam (1856–1932). His poems use dialogic modes of encountering the other on various levels which all relate back to his conversion to Islam. The dialogic encounters with the other open up a contact zone in which the interaction between self and God, self and religious community as well as self and non-Muslim discursive environment can unfold. The conversion experience is a driving force in Quilliam's work, allowing the speaker to construct – through various perspectives – a dynamic as well as fleeting location of the hybrid convert self in relation to British society. The act of conversion, again, constitutes a radical response in articulating the self in a new relationship to God. Simultaneously, the speaker's poetic strategies reflect his location within a religious minority and implicitly show how he re-interprets the community's relation to the religious majority. The speaker's performative act of conversion designs a complex network of relationships through which human interaction as well as the relation of God and human being are negotiated. Herein, dialogic encounters become a poetic means for capturing the presence of God in relation to the convert self.